Review of Hybrid Contract of Sharia Banking from the Perspective of Maqashid Syariah - Kamaluddin, Imam; Ismail, Taufiq (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2024)
Background. Multi-contract (hybrid contract) is currently widely applied in Sharia Banking. The contract is used in various transactions in Sharia Banking products such as the Ijarah Muntahiyah Bit Tamlik and Musyarakah Mutanaqishah contracts. In practice, the application of the multi-contract raises schematic problems, but Sharia Banking still applies the contract. It is interesting to study the practice of multi-contract in Sharia Banking from the aspect of maqasis sharia. Maqasid sharia analysis is used to see the maslahah side. Aim. This study aims to review the practice of multi-contract in Sharia Banking in the perspective of maqasid sharia. Methods. This study uses library research. Results. The results of this study indicate that the jurists (fukaha) agree on the permissibility of multi-contracts, but the validity of the results of the merger depends on what contracts are combined. The elements prohibited by the maqashid sharia in this hybrid contract include coercion, elements of fraud to gain profit, and no one is harmed between the two parties.